Identification of autophagy-related genes in intestinal ischemia-reperfusion injury and their role in immune infiltration - Hu, Yichen; Zou, Qinghua; Sun, Yanbo; Li, Weiming; Yin, Zhaochuan; Zhao, Yuanpei; Shi, Kaiwen; Liu, Hongyuan; Wang, Jiahui (Frontiers in Physiology, 2025)
BackgroundIntestinal ischemia-reperfusion (II/R) injury is a serious condition characterized by high morbidity and mortality rates. Research has shown that II/R injury is closely linked to autophagy and immune dysregulation. This study aims to investigate the potential correlations between autophagy-related genes and infiltrating immune cells in II/R injury.MethodsGSE96733, GSE37013, and autophagy-related genes were obtained from the Gene Expression Omnibus (GEO) and the Human Autophagy Database, respectively. Subsequently, the biological functions of the differentially expressed genes (DEGs) were explored through DEGs analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, and Gene Ontology (GO) analysis. Using R software, human autophagy-related genes were converted to their mouse homologous autophagy-related genes (ARGs). The DEGs were then intersected with ARGs to obtain differentially expressed autophagy-related genes (DEARGs). To identify hub genes, protein-protein interaction (PPI) network analysis, Lasso regression, and random forest methods were employed. A nomogram model was constructed to assess its diagnostic value. Following this, immune infiltration analysis was performed to evaluate the potential correlation between Hub genes and immune cell infiltration. Additionally, a hub gene-related network was constructed, and potential drugs targeting hub genes for the treatment of II/R injury were predicted. Finally, the expression levels of hub genes in a mouse model of II/R injury were validated through dataset verification and quantitative real-time polymerase chain reaction (qRT-PCR).ResultsOur analysis identified 11 DEARGs. Among these, 5 DEARGs (Myc, Hif1a, Zfyve1, Sqstm1, and Gabarapl1) were identified as hub genes. The nomogram model demonstrated excellent diagnostic value. Immune cell infiltration analysis indicated that these 5 hub genes are closely associated with dendritic cells and M2.Macrophage. Furthermore, the regulatory network illustrated a complex relationship between microRNAs (miRNAs) and the hub genes. Additionally, trigonelline and niacinamide were predicted as potential therapeutic agents for II/R injury. In both dataset validation and qRT-PCR validation, the four hub genes (Myc, Hif1a, Sqstm1, and Gabarapl1) showed consistency with the results of the bioinformatics analysis.ConclusionMyc, Hif1a, Sqstm1, and Gabarapl1 have been identified as ARGs closely associated with immune infiltration in II/R injury. These hub genes may represent potential therapeutic targets for II/R injury.